PENGARUH PAJAK, TUNNELING INCENTIVE, MEKANISME BONUS DAN LEVERAGE TERHADAP KEPUTUSAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2018 - Akmaliyah, Nurus Shobah; Muiz, Enong; Rahayu, Dewi Pudji (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
AbstrakThis study aimed to determine the effect of Tax, Tunneling Incentive, Bonus Plan and Leverage on Transfer Pricingdecision. In this study used methods of explanation. The variables studied are Tax, Tunneling Incentive, Bonus Plan and Leverage as the independent variables Transfer Pricing as the dependent variable. The research population is consumer goods industry sector manufacturing as many as 10 companies. Data collection techniques used were document analysis method that examines the financial statements of the Indonesia Stock Exchange (IDX) websites (www.idx.co.id). Data analysis and processing techniques used are descriptive statistical analysis, regretion logistic analysis (regretion logistic model, appropriateness regretion model, assessment all of fit model, coefisient determination, classification matrix. The test results show that the variable Tax have a partial effect on the Transfer Pricingdecision with a significant value of less than 0.05. While the Tunneling Incentive, Bonus Plan and Leverage has a significant value greater than 0.05, it is stated that there is no significant effect on the Transfer Pricing decision..